2010
DOI: 10.1017/s1368980010000170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea, black tea and Rooibos tea on angiotensin-converting enzyme and nitric oxide in healthy volunteers

Abstract: Objective: Tea has been reported to reduce cardiovascular mortality, but the underlying mechanisms are largely unknown. The aim of the current project was to investigate the effect of green tea (Japanese Sencha), black tea (Indian Assam B.O.P.) and Rooibos tea (South Africa) on angiotensin-converting enzyme (ACE) and nitric oxide (NO). Design: Seventeen healthy volunteers received a single oral dose of 400 ml green tea, black tea or Rooibos tea in a randomized, three-phase, crossover study. ACE activity and NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 52 publications
(72 reference statements)
2
42
1
Order By: Relevance
“…Rooibos consumption has been shown to significantly improve the lipid profiles and redox status in humans at risk for developing cardiovascular disease [34]. In addition, it has been shown by Persson et al [35] that Rooibos significantly inhibits angiotensin-converting enzyme (ACE) activity after an oral intake of a single dose of Rooibos tea, supporting the potential role of Rooibos in the overall management of cardiovascular and metabolic-related diseases. Rooibos has been shown to have beneficial effects on glucose homeostasis and type 2 diabetes, with aspalathin stimulating glucose uptake in muscle tissues as well as insulin secretion from pancreatic ␤-cells [36].…”
Section: Introductionmentioning
confidence: 96%
“…Rooibos consumption has been shown to significantly improve the lipid profiles and redox status in humans at risk for developing cardiovascular disease [34]. In addition, it has been shown by Persson et al [35] that Rooibos significantly inhibits angiotensin-converting enzyme (ACE) activity after an oral intake of a single dose of Rooibos tea, supporting the potential role of Rooibos in the overall management of cardiovascular and metabolic-related diseases. Rooibos has been shown to have beneficial effects on glucose homeostasis and type 2 diabetes, with aspalathin stimulating glucose uptake in muscle tissues as well as insulin secretion from pancreatic ␤-cells [36].…”
Section: Introductionmentioning
confidence: 96%
“…Finally, green tea was the only plant type included in this study for which an IC 50 could be determined in both ACE and AngII-AT 1 R in vitro assay methods. Cardiovascular protection attributed to tea flavonoids has been widely reported and shown to involve a range of possible mechanisms (Stangl, Lorenz, & Stangl, 2006) including via RAS (Persson et al, 2010), however the link to AngII receptor binding inhibition has not previously been noted. angiotensin II (AngII) to angiotensin type 1 receptor (AT 1 R) competitive inhibition measured under standard assay conditions, at a final nominal concentration of 5 mg/mL total solids, versus total polyphenolics (TPP) content reported in gallic acid equivalents (mg per 100 mg sample), for a selection of 24 individual Stage 1-processed plant products, representing 11 taxonomic families.…”
Section: At 1 R Regulation By Dietary Plantsmentioning
confidence: 99%
“…ACE inhibition by tea extracts has been recently shown to depend strongly on processing due to effects on polyphenolics (Dong, Xu, Liang, Head, & Bennett, 2011;Murakami et al, 2011;Ranilla, Kwon, Apostolidis, & Shetty, 2010) and supports data showing in vitro bioactivity of enzyme and heat-modified black tea (prior to application of Stage 1 processing) was lower than green tea (Table 2). Catechin 3-O-gallate from green tea was shown to inhibit ACE by noncompetitive kinetics (Liu et al, 2003) with other mechanisms of BP regulation shown by tea polyphenolics including via NO-mediated vasodilation (Negishi et al, 2004;Persson, Persson, Hagg, & Andersson, 2010). However, the capacity for in vivo regulation of RAS by tea polyphenolics was supported by studies with normotensive (Persson et al, 2010) and mildly hypertensive subjects (Kurita, Maeda-Yamamoto, Tachibana, & Kamei, 2010) where BP lowering correlated with ACE inhibition.…”
Section: Ace Regulation By Dietary Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that tea is very useful for health, (1)(2)(3)(4) but few people know that many types of tea, such as black tea, green tea, and oolong tea, come from the same plant and their taste depends on the manufacturing process. One of the key steps in the tea manufacturing process, which is a factor in determining the types of tea, is the degree of fermentation.…”
Section: Introductionmentioning
confidence: 99%